Hookah steam stones: smoking vapour expands from electronic cigarettes to waterpipes - Lee, Youn Ok; Mukherjea, Arnab; Grana, Rachel (Tobacco control, 2013)
The most detailed information available come from an industry website indicating that steam stones 'carbonize at the temperature found in a hookah and, therefore, release (sic) pyrolysis' and emit fog from "1,2-propanediol or glycerol." ( http://www.steam-stones.info ) In addition, smoking steam stones in most hookahs involves using charcoal as the heat source resulting in the inhalation of charcoal smoke, a major source of carbon monoxide (CO) and carcinogenic polyaromatic hydrocarbons (PAH).